Use of non-thermal microwave plasma for syngas production from dry reforming of compressed biomethane - E. Chaiya (2018)
Synthetic gas or syngas produced from reforming of hydrocarbon fuels can be used to generate ammonia, pure H2 and liquid fuels such as methanol, gasoline and diesel in downstream processes. In this study, a laboratory scale microwave discharge system was used to reform compressed biomethane into syngas. Interaction between non-thermal plasma with biomethane constituents (CH4 and CO2 at mixture volume ratio of 90: 10 was carried out at varying flow rates of 0.5-3 lpm. The product gas obtained was analyzed by gas chromatograph. It was found that yields and conversions were peaked at a flow rate of 1.5 lpm. The maximum conversions of CH4 and CO2 were 35 and 61%, and the maximum yields of H2 and CO were 11 and 2%, respectively. © Research India Publications.